We are required to write an inequality for the expression and also solve it
The number y is at least 10.9
let
the unknown number = y
The sum of a number y and 6.2 = y + 6.2
y + 6.2 ≤ -4.7
y ≤ -4.7 - 6.2
y ≤ 10.9
Therefore,
The expression is represented by the inequality y + 6.2 ≤ -4.7 and y ≤ 10.9
Read more:
brainly.com/question/15816805
Answer:well i do know what exaclty what you were reading so i have no clue add a coment about it ill read then answer :)
Step-by-step explanation:
----------------------------
Answer:
Hello! I believe your answer is a = 3
Step-by-step explanation:
a=
= 3
Have a good day! - Zac
Answer:
253,000
Step-by-step explanation:
- Plug the above answers in: 2.1 × 100,000 + 4.3 × 10,000
- 2.1 × 100,000 = 210,000
- Plug 210,000 in: 210,000 + 4.3 × 10,000
- 4.3 × 10,000 = 43,000
- Plug 43,000 in: 210,000 + 43,000
- 210,000 + 43,000 = 253,000
I hope this helps!